2022
DOI: 10.1136/jitc-2022-005755
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lifileucel, a one-time autologous tumor-infiltrating lymphocyte (TIL) cell therapy, in patients with advanced melanoma after progression on immune checkpoint inhibitors and targeted therapies: pooled analysis of consecutive cohorts of the C-144-01 study

Abstract: BackgroundPatients with advanced melanoma have limited treatment options after progression on immune checkpoint inhibitors (ICI). Lifileucel, a one-time autologous tumor-infiltrating lymphocyte (TIL) cell therapy, demonstrated an investigator-assessed objective response rate (ORR) of 36% in 66 patients who progressed after ICI and targeted therapy. Herein, we report independent review committee (IRC)-assessed outcomes of 153 patients treated with lifileucel in a large multicenter Phase 2 cell therapy trial in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 56 publications
2
49
0
Order By: Relevance
“…Recent efforts to scale this approach with private sector investment have permitted clinical trials to be conducted by a significantly larger number of treatment centers. And, the same durable response rates, if not modestly higher, have been observed even among patients who have received and failed to response to immune checkpoint antibody therapy and BRAF inhibitor-based treatment (for those with BRAF-V600 mutations; Chesney et al, 2022). It is expected that this approach will receive FDA approval, permitted its more widespread use, though still somewhat limited to centers with the ability to manage highdose IL-2 toxicity.…”
Section: Cellul Ar Ther Apy and Immune Checkp Oint B Lo Ck Adementioning
confidence: 92%
“…Recent efforts to scale this approach with private sector investment have permitted clinical trials to be conducted by a significantly larger number of treatment centers. And, the same durable response rates, if not modestly higher, have been observed even among patients who have received and failed to response to immune checkpoint antibody therapy and BRAF inhibitor-based treatment (for those with BRAF-V600 mutations; Chesney et al, 2022). It is expected that this approach will receive FDA approval, permitted its more widespread use, though still somewhat limited to centers with the ability to manage highdose IL-2 toxicity.…”
Section: Cellul Ar Ther Apy and Immune Checkp Oint B Lo Ck Adementioning
confidence: 92%
“…CR and PR were observed in 5% and 26% of patients, among those who responded to the treatment. Median overall survival and progression-free survival were 13.9 and 4.1 months, respectively [26].…”
Section: Til Therapymentioning
confidence: 98%
“…Recently, a phase II study was published showing results of lifileucel in patients with advanced melanoma after several lines of therapy, including checkpoint inhibition and targeted therapies if BRAF mutated. 41 In this study, 153 sequentially enrolled patients, 66 from a previously reported cohort 42,43 with a longer follow-up and 87 newly reported patients, were pooled for analysis with a median of 3.0 lines of prior therapies. Of these, 81.7% had received both anti-PD-1 and anti-CTLA-4.…”
Section: History Of Clinical Developmentmentioning
confidence: 99%
“…Moreover, another question that remains is whether TIL therapy would be as effective after pretreatment with anti–PD-1/anti–CTLA-4 combination therapy. Recently, a phase II study was published showing results of lifileucel in patients with advanced melanoma after several lines of therapy, including checkpoint inhibition and targeted therapies if BRAF mutated 41 . In this study, 153 sequentially enrolled patients, 66 from a previously reported cohort 42,43 with a longer follow-up and 87 newly reported patients, were pooled for analysis with a median of 3.0 lines of prior therapies.…”
Section: Tumor-infiltrating Lymphocyte Therapymentioning
confidence: 99%